Optical and hydroacoustical measurements of bubble-flow seepage offshore Oregon (~46° N) during RV FALKOR cruise FK190612 - Mario Enrique Veloso-Alarcón; Peter Urban; Tim Weiß; Kevin Köser; Mengkun She; Jens Greinert (PANGAEA, 2022)
Two lander-based devices, the Bubble-Box and GasQuant-II, were used to investigate the spatial and temporal variability and total gas flow rates of a seep area offshore Oregon, United States. The Bubble-Box is a stereo camera–equipped lander that records bubbles inside a rising corridor with 80 Hz, allowing for automated image analyses of bubble size distributions and rising speeds. GasQuant is a hydroacoustic lander using a horizontally oriented multibeam swath (Imagenex DeltaT) to record the backscatter intensity of bubble streams passing the swath plain. The experimental set up at the Astoria Canyon site at a water depth of about 500m aimed at calibrating the hydroacoustic GasQuant data with the visual Bubble-Box data for a spatial and temporal flow rate quantification of the site. For about 90h in total, both systems were deployed simultaneously and pressure and temperature data were recorded using a CTD as well. The data presented here contain post-processed information collected with the two lander-based devices during the cruise FK190612 on board RV FALKOR from the Schmidt-Ocean Institute in June 2019 (https://schmidtocean.org/cruise/methane-seeps-at-edge-of-hydrate-stability/). The first dataset contains post-processed ASCII information of the optic data recorded with the Bubble-Box system during two deployments (BBM-11 and BBM-17) and includes overall results of bubble sizes, volumes, rising speeds and flow rates of the observed bubble streams. A second dataset contains the acoustic backscatter of a seep site collected with the GasQuant II system during two deployments (GQM-3 and GQM-4). Each file contains the uncalibrated backscatter averaged in time (1 minute average) of the original dataset recorded with the GasQuant II. Files are provided in the Imagenex DeltaT data output format (*.83b) and can be easily visualized and inspected using FMMidwater (QPS) .